THE EFFECT OF MODELS OF READING AND STUDENTS’ ATTITUDE ON STUDENTS’ ACHIEVEMENT IN INFERENTIAL READING COMPREHENSION - Dina Irmayanti Harahap; Nining Sudarwita (Journal MELT (Medium for English Language Teaching), 2021)
The objectives of this study were to investigate whether (1) Achievement in Inferential Reading Comprehension which taught with Miscue Analysis is higher than Interactive Compensatory Model (2) Achievement in Inferential Reading Comprehension with Positive attitude is higher than students’ with negative  attitudes and (3) Interaction between Models of reading and students’ attitudes on the students’ Achievement in Inferential reading comprehension. A quantiative research was carried in a combination with an experimental and descriptive research. Two hundred and fourty  students in semester 5 of  2007/2008 Aademic Year were choosen as the sample by using random sampling technique, 90 students were divided into three groups of 30 ( 2 groups as experimental group and 1 group as control group). First, a pre-test was administered for all groups, then the first experimental group was treated by using Miscue Analysis, the second experimental group by using Interactive Compensatory Model, and the control group by using traditional method or conventional way. After 12 meetings, a post-test was conducted for all groups to evaluate the students’ achievement. Finally, the reseacher conducted questionnaires and indepth interview to identify students’ attitude toward inferential reading comprehension. The data were analyzed by applying two-way ANOVA for the experimental research. It was also computed by using the SPSS and MINITAB Statistics Softwares. The result of testing the first hypothesis shows that Fobserved is greater than Ftable (7.858 > 3.98). It was found that Miscue Analysis is the most effective method. It can be seen from the highest one among the methods and strenghten by using Neuman Keuls formula. In conclusion, the Miscue Analysis and Interactive Compensatory Model  significantly affected students’ inferential reading comprehension. Based on the questionnaires data, after converting the students’ questionnaires result into numerical data using Lykert-type scale, it was found that students’ had positive attitude toward reading in the “positive highly” category, in the value of 131 between 100-150. This analysis followed by comparing the results of questionnaires with students’ post-test results manually by using Pearson formula and by MINITAB analysis. It was found that there was positive correlation between students’ attitude and students’ inferential comprehension achievement. In other words, students’ attitude had strong relationship with students’ reading inferential comprehension achievement. It is to say that the more positive the students attitude, the better their inferential reading comprehension will be.